Melatonin: A Novel Indolamine in Oral Health and Disease - V. K. Chava; K. Sirisha (Hindawi Limited, 2012)
This paper attempts to summarise the findings accumulated within the last few years concerning the hormone of darkness "melatonin." Based on its origin, from the pineal gland until recently it was portrayed exclusively as a hormone. Due to its lipophilic nature, it is accessible to every cell. Thus, in the classic sense it is a cell protector rather than a hormone. Recent studies, by Claustrat et al. (2005), detected few extrapineal sources of melatonin like retina, gastrointestinal tract, and salivary glands. Due to these sources, research by Cutando et al. (2007), is trying to explore the implications of melatonin in the oral cavity, in addition to its physiologic anti-oxidant, immunomodulatory and oncostatic functions at systemic level that may be receptor dependent or independent. Recently, certain in vivo studies by Shimozuma et al. (2011), detected the secretion of melatonin from salivary glands further emphasising its local activity. Thus, within our confines the effects of melatonin in the mouth are reviewed, adding a note on therapeutic potentials of melatonin both systemically and orally.